THE OCCURRENCE OF DEPRESSION AMONG STUDENTS IN UNIVERSITY OF CYBERJAYA DURING MOVEMENT CONTROL ORDER (MCO) OF COVID-19 PANDEMIC - Ang, Yien Weon; binti Alffian, Hidayatul Athifah; bin Muhammad Khairulnizam , Nik Muhammad Syaraf; Manaharan, Thamilvaani (Malaysian Journal of Public Health Medicine, 2022)
In this study, we demonstrate the prevalence of depression and factors associated with depression among foundation students in University of Cyberjaya during Movement Control Order (MCO) of Covid-19 Pandemic. A cross-sectional study was conducted from July 2021 to February 2022, a period where phase three of MCO was declared in Malaysia. Data was collected by using online Patient Health Questionnaire-9 as the scoring system for depression and was analysed using Jeffrey’s Amazing Statistics Program (JASP) version 0.14.1.0. Statistical analyses such as descriptive analysis, chi- square and multinomial logistic regression was applied in this study. Our result showed that the prevalence of depression among foundation students during MCO was high. The students enrolled in Foundation in Art program reported to have the highest severe depression compared to the other foundation programs. Although sociodemographic factors exhibited relevant prevalence pattern among the foundation students, however there is no significant (*p<0.05) association between sociodemographic factors with prevalence of depression in this study. We further analysed the following predominant factors which could affect the learning process and root cause of depression among the students during MCO. Interestingly, students unsatisfied with online classes (*p=0.028) and have poor internet connection (*p=0.027) revealed significant association with depression level. Thus, in order to improvise the learning outcomes, we suggest to have an interactive learning and blended teaching method to overcome the depression and mental stress in students.